2015
DOI: 10.1590/0100-83582015000200024
|View full text |Cite
|
Sign up to set email alerts
|

Influência de Adjuvantes e Pontas de Pulverização na Deriva de Aplicação do Glyphosate

Abstract: Além do impacto ambiental, a deriva de glyphosate pode causar danos sobre culturas sensíveis a esse herbicida. O objetivo deste estudo foi avaliar a influência de adjuvantes e pontas de pulverização na deriva de glyphosate aplicado via terrestre. O estudo foi conduzido em campo, arranjado em esquema fatorial (3 x 9), sendo o primeiro fator constituído por três pontas de pulverização: uma de jato plano (Teejet XR 110.015) e duas de jato plano com indução de ar (Teejet AIXR 110.015 e Teejet TTI 110.015). O segun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
3
0
5
Order By: Relevance
“…The air induction nozzles are well known tools designed to produce a greater proportion of large-diameter spray droplets as well as fewer drift-prone, fine spray droplets (McGinty et al 2016). For example, the application of several chemicals through the AIXR nozzles increased the VMD in all situations compared to the standard XR nozzle (Ferguson et al 2015;Martini et al 2015). In another study, both 2,4-D choline and DMA formulations showed lower drift potential when applied through the ADIA nozzle (flat fan with air induction) in relation to the XR nozzle (Contiero et al 2016).…”
Section: Spray Drift-affected Areamentioning
confidence: 99%
“…The air induction nozzles are well known tools designed to produce a greater proportion of large-diameter spray droplets as well as fewer drift-prone, fine spray droplets (McGinty et al 2016). For example, the application of several chemicals through the AIXR nozzles increased the VMD in all situations compared to the standard XR nozzle (Ferguson et al 2015;Martini et al 2015). In another study, both 2,4-D choline and DMA formulations showed lower drift potential when applied through the ADIA nozzle (flat fan with air induction) in relation to the XR nozzle (Contiero et al 2016).…”
Section: Spray Drift-affected Areamentioning
confidence: 99%
“…In terms of time of applying and biological target control, the questionnaire showed that 89.29% of the interviewees are not used to monitoring weather conditions through thermohygrometers during the application. However, 82.14% of them declared being aware of the ideal weather conditions for the application, which are temperature inferior to 30 degrees Celsius, relative humidity (RH) higher than 55.00%, and wind speed until 10 km/h [18]. Some interviewees pointed out just monitoring the efficiency of the product through the extinction of the pests and plant disease vectors (94.64%), while others affirmed also doing it during the pesticide application through water-sensitive papers.…”
Section: Resultsmentioning
confidence: 99%
“…No entanto, segundo Cunha et al (2003), as mesmas possuem alto risco de deriva, dependendo das características de pressão e ângulo de abertura. Havendo, portanto, uma tendência pela substituição por aquelas com indução de ar, pois apresentam potencial de deriva menor (MARTINI et al, 2015). As pontas por indução de ar permitem a formação de gotas maiores, atingindo assim, o alvo, com maior facilidade.…”
Section: Introductionunclassified